A preliminary analysis regarding functional mitral regurgitation grading with echocardiography and CMR: in search of similarities and resolving discordances. (3rd October 2022) - Maltes, S; Lima, R; Santos, R R; Freitas, P; Lopes, P M D; Marta, L; Guerreiro, S; Abecasis, J; Ferreira, A; Ribeiras, R; Andrade, M J
Abstract: Background: Functional mitral regurgitation (fMR) severity grading by 2D transthoracic echocardiography (TTE) can be a complex task, especially in patients where PISA assumptions are not met (eg. non-circular orifice or multiple jets). Cardiac magnetic resonance (CMR) can provide further insight on the hemodynamic burden of fMR by accurately determining mitral regurgitant fraction (RegFrac). Our goal was to investigate the concordance and disagreement between the two modalities in assessing fMR. Methodology: Single-center prospective study of fMR patients performing same-day TTE and CMR from Feb to Dec 2021. MR severity was classified according to 2020 ACC consensus: grade I (mild; EROA <0.20 cm 2 ), grade II (moderate; EROA 0.20–0.29 cm 2 ), grade III (moderate-to-severe; EROA 0.30–0.39 cm 2 ) and grade IV (severe; EROA ≥0.40 cm 2 ). MR assessment by CMR was determined through regurgitant volume (RVol) and RegFrac quantification. A RegFrac ≥35% (recently shown as the best cut-off for prognostication) was considered hemodynamically significant. Results: A total of 36 patients were included (age 65±14y; 74% male; left ventricle [LV] ejection fraction by TTE and CMR 35±13% and 34±11%, respectively). Mean RVol and EROA by TTE were 28±11mL and 0.18±0.8 cm 2 . Mean RVol and Regfrac by CMR were 20±13 mL and 25±12%, respectively. A moderate correlation between RVol by TTE and CMR was found (Pearson's R 0.58, p=0.001). According to TTE, there were 20 patients (56%) with grade I fMR, 12 patients (33%) with grade II fMR and 4 patients (11%) with grade III fMR. All patients considered to have mild (grade I) fMR by TTE had a RegFrac <35% at CMR. However, amongst those with moderate and moderate-to-severe (grades II and III) fMR, there were 8 patients (50%) with hemodynamic significant fMR (RegFrac ≥35%) at CMR – see Figure 1. Those with RegFrac ≥35% by CMR had higher indexed LV diastolic (165±24 vs 139±48 mL/m 2 ) and systolic (116±31 vs 95±48 mL/m 2 ) volumes and higher pulmonary artery systolic pressures (48±14 vs 41±16 mmHg) when compared with patients whose RegFrac was <35%, even though statistically significance was not reached. Conclusion: Using the criterion of RegFrac ≥35%, CMR re-classifies (half for each side) the patients with moderate and moderate-to-severe regurgitations by TTE. Recognizing, overcoming and resolving the disagreements between the techniques is the way forward to reach excellence. Funding Acknowledgement: Type of funding sources: None.